Primary biliary cirrhosis in men. Issue 11 (November 1986) - Lucey, M R; Neuberger, J M; Williams, R
Abstract : To determine whether primary biliary cirrhosis differed in men and women we reviewed the presenting features and clinical course of 39 men and 191 women with primary biliary cirrhosis followed at this unit between 1970 and 1984. Age and severity of disease at time of diagnosis were similar in both groups. Pruritus was significantly less common in men than in women both at diagnosis and throughout the period of follow up (p less than 0.01). The difference in incidence of pruritus at diagnosis was most evident when the male group were compared with a group of premenopausal women, an observation which is consistent with involvement of sex steroid metabolism in the origin of pruritus. Skin pigmentation was also less marked in men at diagnosis (p less than 0.05). Autoimmune associated conditions, especially sicca syndrome, were more common in women. Survival was similar among men and women although hepatoma developed significantly more frequently in male patients (p less than 0.01).